Processos evolutivos históricos e recorrentes e seu impacto na distribuição e na conservação de Alouatta (Primates, Atelidae) - Schwantes, Jéssyca Bressan (2024)
Primates perform a crucial role in forest regeneration as seed dispersers. Consequently, the threats these animals face, such as landscape and climate changes, pose significant risks to ecosystem maintenance. However, a more accurate understanding of these threats requires integrative approaches addressing the evolutionary processes that have shaped species distributions in the past to predict better the impacts of climate change and habitat fragmentation in the future. The Alouatta genus has the broadest geographic distribution among the Neotropical primates. Although it has been extensively studied, significant gaps remain in the knowledge involving the genus, such as: (1) Which biogeographic and ecological patterns are associated with Alouatta diversification and distribution?; (2) How might climate change impact the range of the black howler (A. caraya) and how might fragmentation increase risks to its conservation?; and (3) How might the genetic diversity and the geographic distribution of A. guariba, the most threatened species of the genus, be influenced by climate changes, fragmentation, or contact zones with other species? This thesis aims to assess the biogeographic history and the potential distribution of Alouatta, trying to answer the three major questions presented above. Integrative approaches, including molecular and ecological tools, were used for this task. The results indicate Alouatta diversification began approximately 13 million years ago, likely in northwestern Amazonia, driven by niche divergence. Even so, some species exhibit niche overlap patterns, potentially associated with the retention of ancestral niches. Alouatta caraya is one species presenting such a pattern, contributing to its high vulnerability to climate change. Future projections for the species predict a continuous decrease in climatically suitable areas from 2021 until 2100. Furthermore, less than 11% of its potential range is currently protected, with the highest suitability areas located in the Chaco and Pampa, regions that have experienced significant habitat conversion over the last 35 years. For A. guariba, current genetic diversity reflects the current patterns of climatic suitability, with future projections suggesting a decline in these correlations influenced by variables such as precipitation and seasonality. The main threats to A. guariba include habitat fragmentation associated with agricultural and urban expansion. We recommend conservation measures in areas with high genetic diversity and climate risk to ensure effective monitoring and protection. After all, the conservation of different Alouatta species is essential in the face of climate change and habitat fragmentation. Protecting areas with high genetic diversity and adopting environmentally responsible management practices are crucial to ensuring the survival of these species and the health of ecosystems. Implementing these measures will be critical to addressing the challenges threatening biodiversity in the Neotropical region.